Perancangan Sistem Pakar Penyakit Pada Ayam Broiler Berbasis Website Dengan Menggunakan Metode Forward Chaining - Saputra, Dedi; Ari Masyhuri , Ahmad (CV. Shofanah Media Berkah, 2023)
Broiler chicken is one of the poultry that is used for meat by many people, so many people see the potential in the business and start raising broiler chickens. However, in raising this type of broiler, chicken cannot be separated from the risk of disease originating from viruses or bacteria that make the results of the farm not optimal and tend to lose money. In some large farms there is already a veterinarian to treat the disease, but in small farms or for novice breeders in rural areas, they do not have veterinarians and there is rarely counseling about diseases that attack broiler chickens. This is an obstacle for farmers making an early diagnosis of diseases that attack broiler chickens and can cause livestock yields to be not optimal. In this case, overcoming these obstacles, broiler chicken farmers need a knowledge-based system to find out disease information by diagnosing the symptoms that arise, an expert system which is part of the developed environment, and an expert consultation environment made by researchers in an effort to facilitate consultation of various diseases suffered by broiler chickens. after a thorough diagnosis. There are 2 (two) inference engines, namely the forward chaining method and the backward chaining method. Judging from the object of research, namely broiler chickens, the author decided to use the forward chaining method. The forward chaining method is a search/drawing of conclusions based on existing data or facts and leading to a conclusion. The search starts from the existing facts and then moves forward through the premises to reach a conclusion or bottom-up reasoning. This method is able to provide a lot of information from a small amount. From the results of this study, it can be concluded that 92.9% of respondents agree that this website is very effective for diagnosing diseases in broiler chickens and easy for broiler breeders to understand.